2001
DOI: 10.1002/jpp.312
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orbitals and electronic spectra of benzo-fused and related porphyrin analogues

Abstract: Molecular orbital (MO) calculations of more than 60 porphyrinic p conjugated structures have been performed within the framework of the Pariser-Parr-Pople approximation. The results of a series of compounds are introduced and summarized in order to show how they vary depending on the systematic change in molecular structure. These are shown schematically or itemized. Our results are compared with the spectra of the corresponding known compounds and with the MO results reported by previous workers, if available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 46 publications
(55 reference statements)
7
32
1
1
Order By: Relevance
“…The optical properties of 247 are similar to those of analogous heteroatom-functionalized pzs, the H 2 ½pzðtrans-A 2 B 2 Þ pzs, where A and B represent two types of moieties appended trans to each other on the pz periphery (13,14); for 247, A ¼ ð2R; 3RÞ 2,3-dimethyl-2,3-dimethoxy-1,4-diox-2-ene; B ¼ α; α 0 -diisopropoxy benzo (15). Pz 247 exhibits three major optical absorptions, the Soret band (329 nm) and two NIR Q-bands, Q x ¼ 702 and Q y ¼ 629 nm (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The optical properties of 247 are similar to those of analogous heteroatom-functionalized pzs, the H 2 ½pzðtrans-A 2 B 2 Þ pzs, where A and B represent two types of moieties appended trans to each other on the pz periphery (13,14); for 247, A ¼ ð2R; 3RÞ 2,3-dimethyl-2,3-dimethoxy-1,4-diox-2-ene; B ¼ α; α 0 -diisopropoxy benzo (15). Pz 247 exhibits three major optical absorptions, the Soret band (329 nm) and two NIR Q-bands, Q x ¼ 702 and Q y ¼ 629 nm (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Similar trends are observed with benzo-substitution of porphyrinA C H T U N G T R E N N U N G oids. [9] A potential drawback in the context of applications such as OTFTs is that benzoporphycenes are, therefore, more susceptible to oxidative attack than the parent porphycenes. This typically results in irreversible oxygenolytic opening of porphyrinoid macrocycles by attack at one of the meso-carbon atoms and the loss of the heteroaromatic properties of the p-system, as is observed during the degradation of chlorophylls and hemes.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Their results showed that the Q bands of these compounds were not so much "pure" oneelectron transitions but combinations of multiple one-electron transitions. As a consequence, the oscillator strengths of the Q bands of these compounds were small due to the canceling of the transition dipoles of the constituent oneelectron transitions.…”
Section: Wwwchemeurjorgmentioning
confidence: 98%
“…: C 73.34, H 6.94, N 9.10; found: C 73.62, H 6.49, N 8.75. 2,3,7,8,12,13,17,: UV/Vis (pyridine): l max (log 10 e) = 393 (sh; 4.68) 416 (5.56), 543 (4.27), 578 nm (4.20). X-ray crystal structure analysis: Single crystals were prepared by slow diffusion of isopropanol into a solution of compound 1 a in CHCl 3 .…”
Section: Cruciform Porphyrin Pentamers Fused With Benzene Units 2a-cmentioning
confidence: 99%